A strategy to promote research and consultancy assignments in the faculty: A case study of the Faculty of Science and Technology Mzumbe University, Tanzania - Sungau, Joseph Joseph (Managing Change at Universities, 2024)
Article published by the Journal of Managing Change at Universities Pages 59